Global energy assessment of the potential of photovoltaics for greenhouse farming. (1st March 2022) - Fernández, Eduardo F.; Villar-Fernández, Antonio; Montes-Romero, Jesús; Ruiz-Torres, Laura; Rodrigo, Pedro M.; Manzaneda, Antonio J.; Almonacid, Florencia
Graphical abstract: We conduct the energy assessment of agrivoltaic (APV) systems at four representative locations with a high crop cultivation greenhouse implantation, i.e. El Ejido (Spain), Pachino (Italy), Antalya (Turkey) and Vicente Guerrero (Mexico), and for representative plant cultivars from 5 different important socioeconomic families of crops, i.e. Cucurbitaceae, Fabaceae, Solanacae, Poaceae, Rosaceae. Our results show that APV systems could have a transparency around 68% without significantly affecting the crops, and could produce an annual energy up to 200 kWh/m 2 . Highlights: The energy assessment of agrivoltaic (APV) systems is carried out. Representative locations with high density of greenhouses are considered. Important socioeconomic families of crops have been investigated. APV technology present average optimal transparencies of around 68% APV systems could produce up to 200 kWh/m 2 without affecting crops. Abstract: Agrivoltaic (APV) systems have emerged as a promising solution to reduce the land-use competition between PV technology and agriculture. Despite its potential, APV is in a learning stage and it is still necessary to devote big efforts to investigate its actual potential and outdoor performance. This work is focused on the analysis of APV systems in agriculture greenhouses at global scale in terms of energy yield. To conduct this study, we introduce here a novel dual APV model, which is projected in four representative locations with a high crop cultivation greenhouse implantation, i.e. El Ejido (Spain), Pachino (Italy), Antalya (Turkey) and Vicente Guerrero (Mexico), and for 15 representative plant cultivars from 5 different important socioeconomic families of crops, i.e. Cucurbitaceae, Fabaceae, Solanacae, Poaceae, Rosaceae. At this stage, semi-transparent c-Si PV technology has been considered due its high efficiency and reliability. The results show that APV systems could have a transparency factor around 68% without significantly affecting the total crop photosynthetic rate. Taking this into account, APV systems would produce an average annual energy around 135 kWh/m 2, and values around 200 kWh/m 2 under a favourable scenario. This could represent a contribution to the total market share between 2.3% (México) and 6% (Turkey), and up to 100% of the consumption demand of greenhouses equipped with heating and cooling (GSHP), and lighting.